الدروس والعبر المستفادة من سير الصحابيات رضوان الله عنهن والاستفادة منها في عصرنا الحاضر: The Lessons and Wisdom Gained from the Lives of the Female Companions (Radi Allahu 'Anhunn) and Benefiting from Them in Our Present Era (Khairulummah, 2024)
This article sheds light on the biographies of noble female companions (Sahabiyyat) to draw lessons and impactful moral guidance that can influence and reform the behaviour of the modern woman, who has strayed from the teachings of true religion due to the intellectual invasion imposed on the Muslim society by forces hostile to Islam. The best path to establishing a righteous Muslim society lies in shaping a virtuous way, pure in character and conduct, who can raise a generation that leads in civilization, progress, and the restoration of what was taken from their lands.
Keywords: biographies; noble; Sahabiyyat; hostile; Islam